2014
DOI: 10.1002/app.40483
|View full text |Cite
|
Sign up to set email alerts
|

Acrylonitrile–butadiene rubber functionalization for the toughening modification of recycled poly(ethylene terephthalate)

Abstract: The incorporation of functionalized acrylonitrile–butadiene rubber (NBR) into recycled poly(ethylene terephthalate) (PET) was introduced as an effective route for modifying the properties of PET and as a new method for PET recycling as well. To achieve modified NBR, glycidyl methacrylate (GMA) was grafted onto NBR with optimized reactive mixing, in which the highest grafting degree and lowest gel content were generated. PET/NBR blends with and without GMA functionalization were produced by melt mixing, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…1,20,21 In the literature, it appears that especially GMA-based impact modifiers are widely used for polyesters (such as PET) because of the reaction tendency between glycidyl functionality and terminal groups of polyesters. 22,23 Xanthos et al 22 used diimidodiepoxide as a novel chain extender for PET and compared reactivity of diimidodiepoxide with that of GMA copolymer. Their results indicated that the reactivity of diimidodiepoxide chain extender is higher than GMA copolymer even at lower loading level.…”
Section: Introductionmentioning
confidence: 99%
“…1,20,21 In the literature, it appears that especially GMA-based impact modifiers are widely used for polyesters (such as PET) because of the reaction tendency between glycidyl functionality and terminal groups of polyesters. 22,23 Xanthos et al 22 used diimidodiepoxide as a novel chain extender for PET and compared reactivity of diimidodiepoxide with that of GMA copolymer. Their results indicated that the reactivity of diimidodiepoxide chain extender is higher than GMA copolymer even at lower loading level.…”
Section: Introductionmentioning
confidence: 99%